Spatial Well‐defined Bimetallic Two‐Dimensional Polymers with Single‐Layer Thickness for Electrocatalytic Oxygen Evolution Reaction. (17th October 2022) - Fa, Dejuan; Tao, Yanhong; Pan, Xin; Wang, Dingjia; Feng, Guangyuan; Yuan, Jiangyan; Luo, Qingqing; Song, Yaru; Gao, Xuejiao J.; Yang, Ling; Lei, Shengbin; Hu, Wenping
Abstract: Innovative bimetallic materials provide more possibilities for further improving the performance of oxygen evolution reaction (OER) electrocatalysts. However, it is still a great challenge to rationally design bimetallic catalysts because there is not a practical way to decouple the factors influencing the intrinsic activity of active sites from others, thus hindering in‐depth understanding of the mechanism. Herein, we provide a rational design of bimetallic Ni, Co two‐dimensional polymer model OER catalyst. The well‐defined architecture, identical density of active sites and monolayer characteristic allow us to decouple the intrinsic activity of active sites from other factors. The results confirmed that the relative position and local coordination environment has significant effect on the synergistic effect of the bimetallic centres. The highest electrocatalytic activity with the turnover frequency value up to 26.19 s −1 was achieved at the overpotential of 500 mV. Abstract : The well‐defined architecture, identical density of active sites, and monolayer characteristic of bimetallic Ni, Co two‐dimensional polymer model oxygen evolution reaction catalysts can decouple the intrinsic activity of active sites from other factors. The experimental and density functional theory simulation show that the relative position and local coordination environment have a significant effect on the cooperation between the metal centers.